The clinical relevance and prediction efficacy from therapy of tumor microenvironment related signature score in colorectal cancer - Jun, Xiang; Gao, Shengnan; Yu, Lei; Wang, Guiyu (Frontiers in Oncology, 2023)
As the third malignancy in the world, the first-line treatment for CRC includes FOLFOX, FOLFIRI, Cetuximab or immunotherapy. However, the drug sensitivity of patients to regimens is different. There has been increasing evidence that immune components of TME can affect the sensitivity of patients to drugs. Therefore, it is necessary to define novo molecular subtypes of CRC based on TME immune components, and screen patients who are sensitive to the treatments, to make personalized therapy possible. We analyzed the expression profiles and 197 TME-related signatures of 1775 patients using ssGSEA, univariate Cox proportional risk model and LASSO-Cox regression model, and defined a novo molecular subtype (TMERSS) of CRC. Simultaneously, we compared the clinicopathological factors, antitumor immune activity, immune cell abundance and differences of cell states in different TMERSS subtypes. In addition, patients sensitive to the therapy were screened out by correlation analysis between TMERSS subtypes and drug responses. Compared with low TMERSS subtype, high TMERSS subtype has a better outcome, which may be associated to higher abundance of antitumor immune cell in high TMERSS subtype. Our findings suggest that high TMERSS subtype is sensitive to Cetuximab and immunotherapy, while low TMERSS subtype is more suitable for FOLFOX and FOLFIRI regimens. In conclusion, The TMERSS model can be used to determine the prognosis of patients, predict the sensitivity to chemotherapy or immunotherapy, and guide the clinical medication of patients.